Hubungan Persepsi Pasien Tentang Komunikasi Terapeutik Perawat Dengan Kepuasan Pasien Terhadap Pelayanan di Ruang Rawat Inap - Martina Helmalia, Syifaa; Rohayani, Lilis; Setiawati, Setiawati; Oyoh, Oyoh; Inayah, Iin (Yayasan Healing and Healthcare Education, 2024)
The implementation of therapeutic communication until now is still not good and only routine. The aim is to determine the relationship between patient perceptions of nurse therapeutic communication and the level of patient satisfaction with services in the inpatient room of Mitra Anugrah Lestari Hospital. This study used a cross sectional research design. The research sample was filled by 77 patient respondents in the inpatient room of Mitra Anugrah Lestari Hospital. The number of samples used was 77 using purposive sampling technique. Data collection was carried out through interviews and questionnaires. Data analysis was performed univariate and bivariate with the Chi Square test. Therapeutic communication was not good at 54 (70.1%) and it was found that patient satisfaction with services was not satisfied at 48 (62.3%). The results of the analysis with the Fisher Exact Test showed that there was a significant relationship between nurse therapeutic communication and patient satisfaction with p value = 0.001 (p ≤ 0.05). It is hoped that the results of this study can be valuable input for Mitra Anugrah Lestari Hospital to be able to monitor and evaluate the service process and improve nurses' service responses, conduct training on renewing nurses' therapeutic communication towards services, hospitals are expected to always monitor the SOP of nurses' therapeutic communication and service excellent.